CHARACTERISTICS OF CHINA'S WATER RESOURCES, THEIR USE AND MANAGEMENT - KHILCHEVSKYI, Valentyn; HOU, Jingyao (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. This article is a continuation of a previous study that characterized the hydrographic features of China. Its purpose is to characterize China's water resources and the challenges associated with their use and management in a country that has been developing rapidly in recent decades.Methods. To write the article, the information posted on the official websites of the Ministry of Water Resources of the People's Republic of China, the Ministry of Ecology and Environmental Protection of the People's Republic of China, the Water Resources Commission of the Yangtze River Basin, and the global information system of the UN FAO – Aquastat-FAO (China profile) were used. The information was processed by statistical methods.Results. There are 9 main groups of river basins on the territory of China. In the north are: Song-Liao (from the names of the Sungari and Liaohe rivers) or Heilong (Amur)-Sungari; Huaihe; Yellow River; Hai Luan; internal river basins. The total average annual internal flow in these 5 groups of river basins is estimated at 535.5 km3, which is almost 20 % of the country's internal renewable water resources. In the south are the Yangtze, Xijiang (Pearl), southwestern and southeastern river basin groups. The total average annual runoff of these 4 groups of river basins is estimated at 2,176.2 km3, which is slightly more than 80 % of the country's. Internal water resources (local surface runoff together with groundwater) amount to 2812.4 km3. Accordingly, for 1 person – 2000 m3/year. Total water resources (local and transit surface runoff together with groundwater) amount to 2839.7 km3. Accordingly, for 1 person – 2011 m3/year. The annual assessment of water resources depends significantly on the water content of the year (amount of precipitation).Conclusions. In China, a policy of integrated water resources management has been implemented, which was manifested in the adoption of the Water Law, in the activation of the work of 6 river basin commissions and one lake basin, the implementation of the "Three Red Lines" strategy, and the introduction of water rights trading. In China, over-exploitation of water resources in the previous period led to rapid depletion of aquifers in important grain-producing areas, significant reductions in river flow, and often severe river pollution. According to official data, the efforts made by government bodies are yielding positive results – the quality of China's surface water continues to improve.
Keywords: water resources; surface water; groundwater; management; "Three Red Lines" strategy; water rights trading; river diversion; China